2022
DOI: 10.3390/ijms232113439
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Evidence of the Potent and Selective Adenosine A2B Receptor Antagonist PSB-603 in Reducing Obesity and Some of Its Associated Metabolic Disorders in Mice

Abstract: The adenosine A2A and A2B receptors are promising therapeutic targets in the treatment of obesity and diabetes since the agonists and antagonists of these receptors have the potential to positively affect metabolic disorders. The present study investigated the link between body weight reduction, glucose homeostasis, and anti-inflammatory activity induced by a highly potent and specific adenosine A2B receptor antagonist, compound PSB-603. Mice were fed a high-fat diet for 14 weeks, and after 12 weeks, they were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Adenosine, acting via the A2B receptor (A2BR), upregulates HIF-1α even in the absence of hypoxia, suggesting a druggable PTSD and CVD target [ 202 ]. Indeed, PSB-603, an A2BR antagonist, has been found to reduce both obesity and the effects of aging, indicating potential beneficial effects for ECs senescence, EVA, and thymic involution, associated with PTSD and CVD [ 203 , 204 ]. In addition, A2BRs modulate EPO synthesis, a hormone endowed with antidepressant and anxiolytic properties of its own [ 205 , 206 ].…”
Section: Potential Interventionsmentioning
confidence: 99%
“…Adenosine, acting via the A2B receptor (A2BR), upregulates HIF-1α even in the absence of hypoxia, suggesting a druggable PTSD and CVD target [ 202 ]. Indeed, PSB-603, an A2BR antagonist, has been found to reduce both obesity and the effects of aging, indicating potential beneficial effects for ECs senescence, EVA, and thymic involution, associated with PTSD and CVD [ 203 , 204 ]. In addition, A2BRs modulate EPO synthesis, a hormone endowed with antidepressant and anxiolytic properties of its own [ 205 , 206 ].…”
Section: Potential Interventionsmentioning
confidence: 99%
“…However, its side effects, such as hyperactivity and heart rhythm disturbances, represent a problem. Kotańska et al [ 43 ] compared the effect of theophylline with that of PSB-603, a specific adenosine A2B receptor antagonist, on high-fat/high-sugar diet-fed mice and demonstrated that both the A2B receptor antagonists significantly lowered the body weights of the mice. However, only PSB-603 was also capable of reducing triglycerides and total cholesterol blood levels in mice, thus suggesting that blocking A2A with a specific antagonist has stronger effects on lipid reduction than non-selective inhibition.…”
mentioning
confidence: 99%